(untitled) (Management and Connections Journal, 2024)
This literature review aims to examine the academic knowledge about the relationships that shape the discourses of higher education institutions in relation to sustainability. We searched for papers published in journals between 2010 and 2023 in internationally recognized databases, which specifically investigated communication and organizational discourse related to the proposed theme, in institutions of this type. After an initial selection of 383 articles, a total of 65 were analyzed. Through codification and an analysis that sought intentions, silences and directions, several thematic groups and two predominant discourses emerged: one linked to positivist/functionalist epistemological currents and the other related to decolonial studies and the relevance of power relations. With the results obtained, it is expected to broaden the readers’ perspective in relation to the discursive activity performed by this type of organization, regarding a relevant and widely addressed theme inside and outside its limits.